2016
DOI: 10.1016/j.pharep.2016.06.015
|View full text |Cite|
|
Sign up to set email alerts
|

Pharmacological profile of dexketoprofen in orofacial pain

Abstract: The findings of this study demonstrate activation of NO and 5-HTpathways play important roles in the systemic antinociceptive effect of DEX in a murine model of inflammatory pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…In this occasion, the tests used were tonic pain (acetic acid writhing test), phasic pain (tail flick test) and inflammatory pain (orofacial formalin test). Furthermore, results obtained are in agreement with previous reported different profiles of nociceptive activity of NSAIDs in algesiometer tests [7][8][9][10][11][12].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this occasion, the tests used were tonic pain (acetic acid writhing test), phasic pain (tail flick test) and inflammatory pain (orofacial formalin test). Furthermore, results obtained are in agreement with previous reported different profiles of nociceptive activity of NSAIDs in algesiometer tests [7][8][9][10][11][12].…”
Section: Discussionsupporting
confidence: 92%
“…Thereby, among the evidences has been included their interaction with monoaminergic, nitric oxide, endocannabinoids, serotonergic and cholinergic systems and endogenous opioid pathway [13][14][15][16].…”
Section: Discussionmentioning
confidence: 99%
“…The results of our experimental assay showed that dexketoprofen induces a dose‐dependent antinociceptive activity in the acetic acid‐induced abdominal contortions test in mice. Dexketoprofen produced similar antinociceptive activity to that previously reported in the writhing test in mice [22,23], as well as in other animal pain models [24–26]. The antinociceptive potency of the individual drugs was performed by comparing the ED 50 of our study with that of previous reports.…”
Section: Discussionsupporting
confidence: 76%
“…Since the synthesis of optically active drugs is costly, the production and sale of racemic mixtures has been approved. However, preparations containing drugs as ( S )-isomers are also available, e.g., dexibuprofen and dexketoprofen 6,7 .…”
Section: Introductionmentioning
confidence: 99%